Learner autonomy and English language proficiency among Iranian postgraduates in selected universities in Malaysia - Neissi, Sina (2017)
This study investigated the relationship between learner autonomy and English language proficiency of Iranian postgraduate students studying in three Malaysian public universities; namely, Universiti Putra Malaysia (UPM), Universiti Teknologi Malaysia (UTM) and Universiti Kebangsaan Malaysia (UKM). Two hundred and twenty-seven Iranian postgraduate students selected through multi stage cluster sampling participated in the study. A mixed method sequential explanatory design was utilized in which a quantitative correlational design was used in the first phase followed by qualitative semi structural interview in the second phase of the study. In the first phase of the study, the Learner Autonomy Profile Short Form (LAP-SH) was used to measure learner autonomy by measuring four constructs i.e. Desire, Resourcefulness, Initiative and Persistence (DRIP). In addition, an English language proficiency test was used to measure the participants’ English language proficiency. In the second phase of the study, 12 participants who had successfully completed both the online survey (LAP) and English language proficiency test took part in semi structured interviews. The qualitative data gathered though the semi structured interviews helped to expand on the results of the quantitative data that had been gathered. The quantitative data obtained through the instruments in the first phase of the study were subjected to both descriptive and inferential statistics. Descriptive statistical analysis was used to describe the mean and standard deviation of the data. Inferential statistics included correlational analysis and multiple regression analysis. The qualitative data obtained in the second phase of the study was analyzed using content analysis in order to identify the themes. The findings of the study revealed that Iranian post graduate students studying in Malaysian public universities are autonomous in their learning. Also a positive significant relationship was found between learner autonomy and English language proficiency providing evidence that learner autonomy is crucial to successful language learning. Furthermore, Persistence was found to be the best predictor of English language proficiency among the learner autonomy constructs signifying the importance of being persistent in language learning. Finally, the findings showed that exhibiting desire, resourcefulness, initiative and persistence helps Iranian postgraduate students to become more proficient in the English language highlighting the importance of the psychological perspective of learner autonomy in language learning. The findings suggest some implications for English language teaching and learning and for predicting academic potentials based on learner autonomy.